PELAKSANAAN PEMBIASAAN INFAQ DALAM PENGEMBANGAN EMPATI ANAK USIA 5-6 TAHUN DI TK AL-MUHAJIRIN CILEGON, BANTEN - Nur Komala, Cicih Wahyu; Fadlullah; Khosiah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of developing empathy in early childhood thru consistent habituation in the school environment. This study aims to describe the implementation of habitual almsgiving in the development of empathy in 5–6-year-old children at Al-Muhajirin Kindergarten in Cilegon, Banten. The research uses a qualitative method with a descriptive approach. The research subjects are the teachers of Group B, Class Samudra. Data collection techniques were carried out thru observation, interviews, and documentation. Data analysis used the Miles, Huberman, and Saldaña model thru data reduction, data presentation, and conclusion drawing. The research results show that the habituation of infaq is carried out thru the stages of planning, implementation, and evaluation, manifested in routine activities, spontaneous activities, teacher modeling, and programd activities. The habituation of infaq plays a role in developing children's empathy, which is demonstrated thru the ability to recognize others' feelings, share, help, and show tolerance. The success of the implementation is supported by the role of teachers, the school environment, and parental involvement, while the obstacles encountered include the inconsistency of some parents in habituating their children to give infaq. The habituation of giving alms has become one of the effective character education strategies in developing empathy in early childhood.